Southern Bluefin Tuna Case - T. G. Saksina (Московский журнал международного права, 2007)
The Southern Bluefin Tuna Award on Jurisdiction and Admissibility of 4 August 2000 on the dispute between Australia/New Zealand and Japan became the first example of the application of compulsory arbitration under Annex VII of the 1982 UN Convention of the Law of the Sea. The Arbitral Tribunal found that it did not have jurisdiction to hear the merits on the grounds that article 16 of the Convention for the Conservation of Southern Bluefin Tuna provided the possibility of recourse to the arbitration only in the case of consent of both parties to the dispute thus excluding compulsory procedures under Part XV of the 1982 UN Law of the Sea Convention. Although the Arbitral Tribunal refused to hear the merits, the decision appeared to be of high importance for evaluation of applicability and effectiveness of the provisions of the Convention related to the compulsory disputes settlement mechanism.Therefore, the article considers all the variants of the settlement of the dispute, including ITLOS proceedings for the prescription of the provisional measures, proceedings of the Arbitral Tribunal and pleadings of the parties as well as the background of the dispute.